Institutionelle Grundlagen der Agrarprotektion: Eine polit-ok̈onomische Analyse der Agrarpolitik in den Mittel- und Osteuropaïschen Lan̈dern - Christian H.C.A. Henning; Kim Carolin Krause; Carsten Struve (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– The impact of political institutions, e.g. the organization of legislature, election and party systems, on agricultural protection has hardly been taken into account explicitly in theoretical and empirical studies, yet. In this framework the paper investigates to what extent political institutions explain observed variances in the political power of the agrarian population in the ten Central and Eastern European Countries / Candidates (CEEC) applying for an accession to the EU. Moreover, it is analyzed to what extent EU-accession will be politically feasible given the specific political and economic framework conditions of the individual states. In particular, empirical analyses imply the following results: (i) The political power of the agrarian population varies significantly among the analyzed countries. (ii) The political weights are significantly determined by political institutions. (iii) Analyzing to what extent EU-accession is politically feasible in the CEEC-states we can show that political feasibility of EU-accession crucially depends on keeping the rule of financial solidarity. Contrary, keeping the rule of financial solidarity implies that future CAP will become even more inefficient in economic terms.
Keywords: 330; Agrarprotektionismus; Agrarpolitik; Interessenpolitik; Institutionenökonomik; Neue politische Ökonomie; EU-Mitgliedschaft; Osteuropa